Factors influencing knowledge management implementation in secondary school: a case study in Malaysia - Lim, Sook Hon; Sabariah Sharif; Rosy Talin; Soon Singh Bikar Singh (2020)
In Malaysia, there has been a lack of empirical studies that highlights knowledge management in secondary school context. Hence, the purpose of this research is to examine the factors that is influencing knowledge management implementation in a secondary school context. The researchers are the instruments and have employed a qualitative case study approach to conduct this research in a selected secondary school in Kota Kinabalu, Sabah. The informants consisted of two language teachers, two ICT facilitators and the school principal. Data were collected through semi-structured interviews, participant observations and document analysis for triangulation and to enhance the trustworthiness of the research findings. The data was then coded, categorized and analyzed into themes through an iterative process. The findings showed that most of the knowledge in school was documented using filing system without uploading to a knowledge repository for future knowledge sharing and leveraging. The major factors emerged from the findings showed that teacher’s behaviour, the role of leader and ICTs expertise team were the main factors in determining the success of knowledge management implementation in the secondary schools. In this study, the lack of developed knowledge management model in the selected secondary schoolwas one of the main challenges of the research which effects the process of collecting data. Hence, this paper provides an indepth understanding of the factors influencing the knowledge management implementation in secondary schools which in turn would provide a better guideline in making knowledge management initiative a success in the secondary school context.